Estimation of Radiation Exposure to Some Iraqi Patients with Hyperthyroidism treated with Radioactive Iodine-131 as an Outpatient Basis - Nafal NazarBahjat1 , Zahraa Neamah Abbas2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A broadly established therapy is radioactive iodine-131 for patients with hyperthyroidism (1). The radioactive iodine-131 dose is given to the patient as a single dose, which leads to a high radiation exposure surrounding the patient’s location for several days, depending on the amount of the received radiation dose, patient’s isolation in a special room is necessary for a period of time until the amount of radiation exposure decreases to an acceptable limits according to the National regulations. This study aimed to obtain a measurable estimation to the amount of radiation exposure resulting from patients treated with iodine-131 and assessment of compliance of patients and their family members to radiation safety instructions (RSI). In this study, (35) Iraqi patients with hyperthyroidism (15 male and 20 female) divided in to three groups according to 131I doses received that ranging from 3.7 to 7.4 GBq (100-200 mCi), the radiation dose rate was measured at different levels of the patient’s body as well as at different periods after receiving the I-131 treatment dose. Results shows that the external dose rates decrease rapidly and as a result, the greater amount of radioactive iodine is disposed of in the urine in the first two days after therapy. Also there is no observed differences appears in the average radiation dose rate (µSv/hr) resulting from patients after giving the dose of iodine-131 between males and females within the same group, while a significant difference was observed in the average dose rate between the divided groups, especially after an hour of giving the dose. Conclusion this study provide an estimation to the amount of radiation exposure resulting from patients for three days post 131I therapy on outpatient basis, also these results enables us to obtain a database that can be used in determining the amount of radiation reflected from patient to family members and contacts. Oral and written radiation safety instructions (RSI) are given in an appropriate way to patients and family members before patient’s discharge.